Pengaruh Kemampuan Inovasi Terhadap Keunggulan Bersaing pada Warung Makan di Desa Cengkong - Galuh Permadi; Enjang Suherman; Flora Patricia Anggela (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Over time, food stalls in the Cengkong Village area reflect the importance of the food sector in the local economy, as well as changes in consumer trends that influence the way food stalls operate and compete. The aim of this research is to find out, analyze and explain how innovation ability influences competitive advantage in food stalls in Cengkong Village. The research design used in this research is descriptive and verification with a quantitative approach. The population in this study were micro, small and medium enterprises in Cengkong Village, Karawang Regency, totaling 120 respondents. Researchers can use samples obtained from a population of 92 respondents. This research analysis uses simple linear regression analysis using the IBM SPSS Statistics 25 tool. Sample calculations are carried out using the Slovin formula. Based on research results, innovation ability (X) has a positive and significant effect on competitive advantage (Y). With the results of a sig value of 0.000 < 0.05 and a tcount value of (7.558 > 1.986), the Ha hypothesis is accepted and Ho is rejected.